Taming wild genomes: perspectives on mechanisms governing differential introgression in exotic rice germplasm and their applications in breeding - Shrestha, Avinash; Stephens, Christian J.; Angeles-Shim, Rosalyn B. (Frontiers in Plant Science, 2025)
Wide hybridization is an important plant breeding strategy that can be used to expand the available genetic variation in present-day crops towards breeding for enhanced agronomic performance. The primary challenge in wide hybridization is the presence of reproductive barriers and genetic incompatibilities that limit the transfer of desirable wild or distant alleles in the genetic background of cultivated plant species. Here we provide perspectives on the possible role of hybrid sterility and gametocidal genes on the observed preferential introgression in exotic germplasm of rice. We argue that while these aberrant introgression and segregation behavior of wild or distant chromosomes presents significant barriers in exploiting ancestral germplasm in breeding, the same mechanisms can also be exploited to enhance the transfer of wild alleles in a cultivated genetic background. Understanding the genetic basis of preferential introgression and segregation in wide hybrids will have serious implications in our ability to capture ancestral genetic variation that can add significant agronomic value to staple crops like rice.